ANALISIS HUKUM TERHADAP PERLINDUNGAN HUKUM BAGI ANGGOTA BRIMOB DALAM PENGENDALIAN UNJUK RASA - Komang Edy Dharma Saputra (Jurnal Ilmiah Raad Kertha, 2025)
The police's role in securing the public from disturbances duringdemonstrations involves directly confronting demonstrators fighting for their rights,which are protected by the 1945 Constitution of the Republic of Indonesia, includingthe right to express opinions and other rights. In such circumstances, the media, whichis expected to act in a balanced manner in reporting and coverage (electronic media),sometimes when police are attacked by anarchic demonstrators, there is no newscoverage. However, when the police react by attacking in self-defense, the coverage isextensive, making it appear as if the police are violating human rights. This has becomea polemic, especially for police officers on duty in the field